2016
DOI: 10.1155/2016/6728237
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mechanical and Wear Properties of LM24/Silicate/Fly Ash Hybrid Composite Using Vortex Technique

Abstract: This work has investigated to find the influence of silicate on the wear behavior of LM 24/4 wt.% fly ash hybrid composite. The investigation reveals the effectiveness of incorporation of silicate in the composite for gaining wear reduction. Silicate particles with fly ash materials were incorporated into aluminum alloy matrix to accomplish reduction in wear resistance and improve the mechanical properties. The LM24/silicate/fly ash hybrid composite was prepared with 4 wt.% fly ash particles with 4, 8, 12, 16,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The figure 1 exposed that the hardness, tensile strength and density of LM24/silicate/fly ash hybrid composite. Keshav Singh et al [36] fabricated the LM24/ B4C (3%, 5% & 7% wt) composites and tested the mechanical properties with varying weight % of reinforcement. For 7% B4C reinforced with remaining wt % of LM24 has improved 94% in impact strength than the base LM24 and Maximum Tensile strength and hardness were obtained.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The figure 1 exposed that the hardness, tensile strength and density of LM24/silicate/fly ash hybrid composite. Keshav Singh et al [36] fabricated the LM24/ B4C (3%, 5% & 7% wt) composites and tested the mechanical properties with varying weight % of reinforcement. For 7% B4C reinforced with remaining wt % of LM24 has improved 94% in impact strength than the base LM24 and Maximum Tensile strength and hardness were obtained.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Squeeze casting technology has been employed to fabricate parts with desired properties (compressive strength, wear resistance) by optimizing casting parameters using the Taguchi method. 1517 A356 alloys belong to the major class of aluminium-silicon alloys, which are widely used in engineering applications (i.e. cylinder liners, engine blocks, pistons, heads and wheels).…”
Section: Introductionmentioning
confidence: 99%
“…Najib Souissi et al. 16 investigated the relationship between the ultimate tensile strength, hardness and process parameters in a squeeze casting 2017 A wrought aluminium alloy through Taguchi method. They revealed that the effects of various casting parameters including squeeze pressure, melt temperature and die temperature were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Senthil and Amirthagadeswaran 15 examined that the experimental results showed that squeeze pressure, die preheating temperature and compression holding time were the significant parameters towards improvement in mechanical properties. Najib Souissi et al 16 investigated the relationship between the ultimate tensile strength, hardness and process parameters in a squeeze casting 2017 A wrought aluminium alloy through Taguchi method. They revealed that the effects of various casting parameters including squeeze pressure, melt temperature and die temperature were studied.…”
Section: Introductionmentioning
confidence: 99%